A view of Santa Clara Valley from the east - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
A view of Santa Clara Valley from the east, from an unidentified location. To the far right, the southern most tip of the San Francisco Bay can be seen. To the far left, a series of smoke plumes can seen in the distance. Throughout the photograph, numerous orchards, houses, water towers, and out-buildings are visible.